MODEL PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN PAI DI SMPN 2 PAMEKASAN - Saiful Arif (TADRIS: Jurnal Pendidikan Islam, 2015)
Abstract: This study describes the Contextual Teaching and  Learning method  for Islamic religion subject at SMPN 2 Pamekasan. This research resulted in: 1) Islamic religion subject teachers perceived the students as subjects of teaching whose knowledge  always developes in accordance with their experience; 2) The clasroom activities of  Contextual Teaching and Learning method was implemented by creating a conducive learning atmosphere while for assessment was carried out thoroughly, on the cognitive, affective and psychomotor aspects; 3) The response of students to the Contextual Teaching and Learning method was good. It was shown from high learning motivation and anthusiastic involvement of the students in the learning, mostly the students reached above of KKM score and possessing good spiritual or social manners. Keywords: model, learning, contextual, PAI